Risk of Pregnancy-related Venous Thrombosis in Carriers of Severe Inherited Thrombophilia - Martinelli, Ida; Legnani, Cristina; Bucciarelli, Paolo; Grandone, Elvira; De Stefano, Valerio; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 2001)
Homozygous carriers of factor V Leiden have an approximately 80-fold increased risk of venous thrombosis. Also double heterozygous carriers of both the factor V Leiden and the prothrombin gene mutations are at high thrombotic risk. The magnitude of the risk of venous thrombosis in pregnant women with the two severe thrombophilic conditions has not been estimated so far. We performed a multicenter retrospective family study in women with homozygous factor V Leiden, double heterozygous factor V Leiden and the prothrombin gene mutation, and women with normal coagulation. Only relatives of index patients with thrombosis formed the study cohort. Fifteen homozygous and 39 double heterozygous women were compared to 182 women with normal coagulation. Venous thrombosis occurred in 3 of 19, 2 of 50 and 1 of 221 pregnancies, respectively. One thrombotic episode occurred in the third trimester, the remaining 5 in the postpartum. The prevalence of venous thrombosis was 15.8% (95% CI 3.4-39.6) for homozygotes, 4.0% (95% CI 0.5-13.7) for double heterozygotes and 0.5% for women with normal coagulation. The relative risk of pregnancy-related venous thrombosis was 41.3 (95% CI 4.1-419.7) for homozygous and 9.2 (95% CI 0.8-103.2) for double heterozygous carriers. In conclusion, homozygous carriers of factor V Leiden and, to a lesser extent, double heterozygous carriers of factor V Leiden and of the prothrombin mutation have an increased risk of venous thrombosis during pregnancy, particularly high during the postpartum period. On the basis of these findings we recommend that these women receive anticoagulant prophylaxis at least in the postpartum, that should perhaps be extended to the whole pregnancy in homozygous carriers.
Keywords: Coagulation; factor V Leiden; prothrombin mutation; pregnancy; puerperium